Determinants of Hypertension: A Cross-Sectional Analysis of Demographic and Physiological Predictors in a Referral Hospital in Iran - Omidi, Fatemeh; Sadeghi, Soheila (Novelty in Biomedicine, 2024)
Background: Hypertension is a leading risk factor for cardiovascular diseases, significantly contributing to global morbidity and mortality. Understanding the determinants of hypertension is crucial for effective prevention and management. This study investigates the relationships between demographic and physiological factors and hypertension status in a cohort of adults. Materials and Methods: A cross-sectional study was conducted with 105 adult participants, comprising 47 hypertensive and 58 non-hypertensive individuals. Data on age, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, and fasting blood sugar (FBS) were collected. Statistical analyses included summary statistics, Pearson correlation coefficients, and logistic regression to identify significant predictors of hypertension. Results: There were significant differences between hypertensive and non-hypertensive groups regarding SBP, DBP, and BMI. Hypertensive individuals had higher mean SBP (141.4 ± 10.5 mmHg) and DBP (86.4 ± 8.0 mmHg) compared to non-hypertensive individuals (118.1 ± 11.5 mmHg and 72.2 ± 6.8 mmHg, respectively; p < 0.001 for both). BMI was also significantly higher in the hypertensive group (36.8 ± 11.8 kg/m² vs. 32.6 ± 9.8 kg/m²; p < 0.001). Age and BMI positively correlated with both SBP and DBP, while HDL showed a significant negative correlation with DBP. Logistic regression analysis identified age (OR = 1.07, 95% CI: 1.05-1.09, p = 0.02), BMI (OR = 1.06, 95% CI: 1.01-1.15, p = 0.01), and LDL (OR = 1.04, 95% CI: 1.00-1.02, p = 0.04) as significant predictors of hypertension. Conclusion: This study reinforces the significant roles of age, BMI, and LDL cholesterol in the risk of hypertension. These findings highlight the importance of targeting these modifiable risk factors through effective interventions to reduce the prevalence and impact of hypertension. Future research should explore the mechanisms linking these predictors to hypertension to develop comprehensive prevention and management strategies.